PENINGKATAN HASIL BELAJAR PENJUMLAHAN MATEMATIKA SISWA KELAS I SDN 04 SERENGSENG TIPE STAD - Rosfiani, Okta; Sabila, Salsa; Ernawan, Reyhan Fachrezy; Fajar, Muhamad; Hafizah, Hafizah; Syafi, Muhammad (FKIP Universitas Al Washliyah Medan, 2025)
This study discusses the application of the Student Teams Achievement Division (STAD) type cooperative learning model to improve the mathematical addition ability of grade 1 students of SDN 04 Serengseng. The STAD model is designed to encourage cooperation between students in small, heterogeneous groups. The learning process begins with the delivery of material by the teacher, followed by group discussion activities where students share their understanding with each other and solve addition problems together. Each student in the group has a role and responsibility to contribute to the success of their team. Teachers act as facilitators who monitor the learning process, provide direction, and ensure the active involvement of all students. In the final stage, students take individual quizzes to assess their understanding, and awards are given to groups that show significant progress. This approach focuses not only on academic outcomes, but also on developing social skills, such as the ability to communicate, collaborate, and appreciate the opinions of others. The STAD learning model is expected to create a fun learning atmosphere, increase students' motivation, and help them understand the concept of addition better. With structured learning, students can strengthen their maths skills while building positive social relationships in the learning environment.